Retrospective analysis of adaptation to retirement: Levels of per-ceived satisfaction and duration of the adaptive process. - Aymerich Andreu, María; Planes Pedra, Montserrat; Gras Pérez, María Eugenia (Anales de Psicología / Annals of Psychology, 2010)
This research attempted to describe, according to the model of Atchley (1975), the experience of the adaptive phases, the changes of life satisfaction levels and the duration of the process and its phases. A total of 30 retired people were interviewed in depth, representated their Life Chart Methodology-retrospective (LCM-r) on the life satisfaction levels and responded to the Life Satisfaction Index. The results show that even though the retirees did not all experience exactly the same adjustment processes, most of the stages were found. It is also noteworthy that during the ad-justment process large fluctuations were observed in the level of satisfac-tion experienced by the participants, but once they had adjusted to retire-ment their degree of satisfaction returned to levels similar to those re-ported before retirement. Substantial differences were also found with regards to the duration of the adjustment process, which fluctuated from six months to more than a year.